2017
DOI: 10.1039/c7ra07804h
|View full text |Cite
|
Sign up to set email alerts
|

Biological fate of food nanoemulsions and the nutrients they carry – internalisation, transport and cytotoxicity of edible nanoemulsions in Caco-2 intestinal cells

Abstract: Internalisation of edible food nanoemulsions by CaCo-2 intestinal cells. The structure of edible nanoemulsions increases five times upon incorporation of reactive/ROS producing nutrients/APIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 80 publications
2
17
0
Order By: Relevance
“…In contrast, when a nonencapsulated compound is added at concentrations above its solubility, it is not able to efficiently reach the microbial cell membranes. This is in agreement with previous data collected by the researchers about the antibacterial or antifungal activity of different EOs in emulsified form, with respect to their free form [33][34][35][36][37][38][39][40][41][42][43][44]. Moreover, it has been suggested that the emulsifier might also play a notable role in the micelle-mediated mass transfer of the EO that is released from the emulsion droplets and/or which permeate through biological membranes .…”
Section: After Preparationsupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast, when a nonencapsulated compound is added at concentrations above its solubility, it is not able to efficiently reach the microbial cell membranes. This is in agreement with previous data collected by the researchers about the antibacterial or antifungal activity of different EOs in emulsified form, with respect to their free form [33][34][35][36][37][38][39][40][41][42][43][44]. Moreover, it has been suggested that the emulsifier might also play a notable role in the micelle-mediated mass transfer of the EO that is released from the emulsion droplets and/or which permeate through biological membranes .…”
Section: After Preparationsupporting
confidence: 92%
“…Different nanoemulsion formulations were tested, whose formulations are described in detail in Table 1. In general, BEO was mixed with CO to prevent Ostwald ripening [30][31][32][33][34][35][36][37][38][39][40], in a weight ratio of 1:1, determined through preliminary experiments. Blank nanoemulsions were prepared by completely replacing BEO with CO. Nanoemulsions were stabilized using different emulsifiers, such as WP, WP in combination with MS (1:1 wt ratio), SE, GMO in combination with T20 (1:1 wt ratio), based on previously tested nanoemulsion formulations [31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Nanoemulsion Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Arechabala et al tested various surfactants against normal human fibroblasts, and in their study, Tween 80 appeared to be the least cytotoxic [29]. It is successfully used in other nanoemulsions with no cytotoxic effect-with applications for skin [30,31] and food [32]. The CBD was evaluated by Petrosino et al in the HaCaT cell line-no effect was observed with 1, 5, 10, and 20 µM of CBD after 6, 12, and 24 h [33].…”
Section: Biological Skin Response In Vitro and In Vivomentioning
confidence: 99%